The influence of carbon nanotube and nano silica on mechanical and microstructural properties of engineered cementitious composites subjected to elevated temperatures - Haroglu, Hasan; Bulut, Metehan; Tanyildizi, Harun (Elsevier, 2025)
This paper researched the influence of carbon nanotubes (C) and nano silica (S) on the elevated temperature performance of engineered cementitious composites (ECC). For this aim, these nanomaterials were employed at 0 %, 0.25 %, 0.50 %, and 0.75 % by weight of cementitious materials in ECC mixtures. The ECCs containing C and S, cube samples with dimensions of 50x50x50 mm, and prismatic samples with dimensions of 50x75x360 mm were cured in plastic bags at 23 f 2 degrees C for 28 days. After this curing period, compressive strength, four-point flexural strength, and ultrasonic pulse velocity (UPV) experiments were carried out on the samples exposed to room temperature (20 f 2 degrees C) and temperatures of 100 degrees C, 200 degrees C, 300 degrees C and 400 degrees C. It was also conducted through scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDAX), and Fourier transform infrared spectroscopy (FTIR) analyses to examine the microstructural changes of the specimens subjected to elevated temperatures. It is seen that the nanomaterial inclusion in ECCs has a positive effect on the mechanical and microstructural properties of ECCs subjected to elevated temperatures. The compressive strength of the 0.75S-ECC -300 degrees C increased by 34.04 % compared to the reference specimen. In addition, the flexural strength of the 0.50C-ECC exposed to 100 degrees C increased by 9.72 % compared to the reference specimen.
Keywords: ECC; Elevated temperatures; Carbon nanotube; Nano silica; Mechanical and microstructural properties